The role ofmerchant credit insurance in processes stimulating the economic security of companies - Dankiewicz, R. (Lviv Politechnic Publishing House, 2017)
In the paper an attempt to present the role of merchant credit insurance in processes that affect the security of business operations of companies has been taken. As a part of the discussion, the areas and sources of the risks have been presented, their overall distribution has been taken into account, and particular attention has been paid to those that could be covered under insurance contracts concluded with credit insurers. The reasons underlying their use have been discussed, taking into account both the specificity of the risk and the benefits of its protection. In the practical part, the results of author’s own research and the conclusions drawn have been presented. The final part of the paper contains conclusions on an attempt to assess the economic viability of merchant credit insurance in the activities of individual companies taking into account the external market conditions in which they operate.
Keywords: credit insurance; risk management; 368